Π-π stacking controlled photochromic/thermochromic properties of salicylaldehyde Schiff base in solid state. (June 2022) - Li, Yuanyuan; Li, Haowen; Jin, Wenhui; Xu, Xinqi; Liu, Huiying; Ding, Yang; Wang, Gang; Zhang, Tingting; Peng, Qiuchen; He, Juan; Hu, Qinggang; Pan, Li; et al.
Abstract: Salicylaldehyde Schiff base is a kind of typical photochromism and thermochromism system with aggregation-induced emission (AIE) characteristic. In this work, three salicylaldehyde Schiff base derivatives of 1 –3 were synthesized, which showed similar emissions but different photochromic/thermochromic properties in solid state. Only compound 1 exhibited reversible photo- and thermo-responsive performances in solid state according to the enol-keto tautomerism upon UV light irradiation and heating. Mechanism study showed that these different photochromic/thermochromic properties were controlled by the π-π stacking structure of adjacent molecules. This work provided a new perspective to understand the photochromic/thermochromic mechanism of salicylaldehyde Schiff base in solid state. Graphical abstract: Image 1 Highlights: Three salicylaldehyde Schiff base derivatives with similar structures were synthesized. They showed similar emissions but different photochromic/thermochromic properties in solid state. The different properties were controlled by the π-π stacking structure of adjacent molecules. Compound 1 was suitable to be used as a material for photo-patterning.